Prevalence of dental caries among 12-14 year old children in Qatar - Mohammed Al-Darwish; Walid El Ansari; Abdulbari Bener (Elsevier, 2014)
Background: To ensure the oral health of a population, clinicians must deliver appropriate dental services, and local communities need to have access to dental care facilities. However, establishment of this infrastructure must be based on reliable information regarding disease prevalence and severity in the target population. Objectives: The aims of this study were to measure the incidence of dental caries in school children aged 12-14 throughout Qatar, including the influence of socio-demographic factors. Materials and methods: A cross-sectional study was conducted in Qatar from October 2011 to March 2012. A total of 2113 children aged 12-14 were randomly selected from 16 schools located in different geographic areas. Three calibrated examiners using World Health Organization (WHO) criteria to diagnose dental caries performed the clinical examinations. Data analyses were subsequently conducted. Results: The mean decayed, missing, and filled teeth index values were respectively 4.62 (±3.2), 4.79 (±3.5), and 5.5 (±3.7), for 12, 13, and 14 year-old subjects. Caries prevalence was 85%. The mandibular incisors and canines were least affected by dental caries, while maxillary and mandibular molars exhibited the highest incidence of dental caries. Dental caries were affected by socio-demographic factors; significant differences were detected between female and male children, where more female children showed dental caries than male children. In addition, children residing in semi-urban areas showed more dental caries than in urban areas. Conclusion: Results indicated that dental caries prevalence among school children in Qatar has reached critical levels, and is influenced by socio-demographic factors. The mean decayed, missing, and filled teeth values obtained in this study were the second highest detected in the Eastern Mediterranean region. Keywords: Prevalence, Dental caries, DMFT index, School children, Qatar